Analysis of The Implementation of Fixed Assets at PT PLN (Persero) Indonesia for The Period of 2022-2023 - Shaila Pratika Sari; Stephanie Imaylia Napitupulu; Meiman Kristian Putra Gulo; Febriani Nur Rahman; Meigia Nidya Sari (International Journal of Economic Research and Financial Accounting, 2025)
This study analyzes the fixed asset management of PT PLN (Persero) for the period 2022-2023, focusing on the addition, depreciation, and write-off of fixed assets. Using a descriptive qualitative method based on a documentation study of the company's financial statements and accounting records, this study found that PT PLN made significant investments to increase electricity production capacity. The straight-line depreciation method provides transparency in recording annual expenses, although a more adaptive approach to asset usage patterns is needed. In addition, the elimination of inefficient fixed assets demonstrates the company's efforts in maintaining the productivity of the asset portfolio. The conclusion shows that optimizing fixed asset management through asset modernization and maintenance is essential to support the company's strategic goals.